2002
DOI: 10.1002/jcb.10257
|View full text |Cite
|
Sign up to set email alerts
|

MT1‐MMP, but not secreted MMPs, influences the migration of human microvascular endothelial cells in 3‐dimensional collagen gels

Abstract: Matrix metalloproteinases (MMPs) and their specific inhibitors the TIMPs play significant roles in angiogenesis. We investigated how the expression of specific MMPs and TIMPs by human microvascular endothelial cells (hmECs) was modulated by culture of the cells in 3-dimensional (3D) type I collagen gels versus 2-dimensional (2D) collagen-coated surfaces. By reverse-transcription polymerase chain reaction (RT-PCR), levels of mRNA for MMPs-1, -2, and -13, MT1-MMP, and TIMPs-1 and -2 were similar in 2D versus 3D … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(41 citation statements)
references
References 41 publications
1
39
0
1
Order By: Relevance
“…TIMP-2 has been shown to suppress MT1-MMPmediated activation of pro-MMP-2 in II-4 cells grown in 2D monolayer cultures. 42 Similar responses to TIMP-1 and TIMP-2 have previously been reported to explain the migratory behavior of endothelial cells, 43 breast cancer cells 44 and HT1080 cells 45 in collagen gels that has been linked to MT1-MMP-mediated proteolytic activity. In addition, our findings support the view that tumor cells embedded in collagen gels can retain their spherical shape in the absence of MT1-MMP-mediated proteolysis.…”
Section: Discussionsupporting
confidence: 56%
“…TIMP-2 has been shown to suppress MT1-MMPmediated activation of pro-MMP-2 in II-4 cells grown in 2D monolayer cultures. 42 Similar responses to TIMP-1 and TIMP-2 have previously been reported to explain the migratory behavior of endothelial cells, 43 breast cancer cells 44 and HT1080 cells 45 in collagen gels that has been linked to MT1-MMP-mediated proteolytic activity. In addition, our findings support the view that tumor cells embedded in collagen gels can retain their spherical shape in the absence of MT1-MMP-mediated proteolysis.…”
Section: Discussionsupporting
confidence: 56%
“…Many studies have indicated that endothelial cells are highly proteolytic during neovascularization (Arroyo and Iruela-Arispe 2010; Davis et al 2002;Ghajar et al 2008;Pepper 2001;Roy et al 2006;van Hinsbergh et al 2006;van Hinsbergh and Koolwijk 2008). Correspondingly, tubulogenesis by endothelial cells is blocked by inhibition of proteases with chemical inhibitors such as GM6001 (Davis et al 2002;Davis and Saunders 2006;Koike et al 2002) and also by tissue inhibitors of metalloproteinases (TIMPs), such as TIMP-2 and TIMP-3 (Koike et al 2003;Saunders et al 2006). Although soluble MMPs (e.g., MMP-1 and -9) are induced in endothelial cells during tubulogenesis, their role in vascular invasion and morphogenesis remains unclear (Davis and Senger 2005).…”
Section: Discussionmentioning
confidence: 99%
“…EGFR has been shown to be expressed in tumor endothelial cells, while undetectable in their normal counterparts, and plays a role in their proliferative phenotype (66). In addition, MT1-MMP is also expressed in angiogenic endothelial cells and is well known to be an important regulator of angiogenesis (3,(11)(12)(13)67). A relationship between MT1-MMP and EGFR has been suggested in various studies.…”
Section: Mt1-mmp Induces Migration Via Egfr Transactivation Mol Cancementioning
confidence: 99%
“…Several lines of evidence suggest that MT1-MMP -dependent proteolysis of both extracellular matrix components (2,3) and cell surface adhesion receptors (4-6) plays an essential role in tumor growth, invasion, and angiogenesis. The overexpression of MT1-MMP enables tumor cell growth in otherwise growthrestrictive, three-dimensional extracellular matrices (7) and promotes cell migration of a number of cancer (8)(9)(10) and endothelial cell lines (11)(12)(13). The short cytoplasmic sequence of MT1-MMP also contributes to the induction of cell migration by the enzyme (9, 10, 13) possibly through activation of the extracellular signal-regulated protein kinase (ERK) cascade (14), endocytosis and trafficking of the enzyme (15,16), and interaction with tyrosine phosphorylated caveolin-1 (17).…”
Section: Introductionmentioning
confidence: 99%